2020
DOI: 10.5296/jpag.v10i2.16589
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communication Technology (ICT) and Economic Growth in ASEAN-5 Countries

Abstract: Digital economy generally refers to a digital technology-based economy. The embrace of digital economy is transforming a nation's economic growth. Countries blessed with successful digitisation will improve their economic performance; hence, it could increase country's GDP growth. In this respect, ASEAN-5 countries becoming a major economic force driver in Asia as well as to the global growth. The goal of this research is therefore to investigate the relationship between ICT and economic growth in the ASEAN-5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…Also, when employing the GMM estimator for the sample of ASEAN nations, ICT variables have positive coefficients on the dependent variable. These results are contrary to some studies on sub-samples of the region that show almost insignificant effects of ICT development when using traditional panel estimation techniques 8,18 . This suggests that when controlling bias such as omitted variables, heteroskedasticity, endogeneity, and auto correlation, the effects of explanatory variables are statistically significant.…”
Section: Conclusion and Policy Implications Conclusioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Also, when employing the GMM estimator for the sample of ASEAN nations, ICT variables have positive coefficients on the dependent variable. These results are contrary to some studies on sub-samples of the region that show almost insignificant effects of ICT development when using traditional panel estimation techniques 8,18 . This suggests that when controlling bias such as omitted variables, heteroskedasticity, endogeneity, and auto correlation, the effects of explanatory variables are statistically significant.…”
Section: Conclusion and Policy Implications Conclusioncontrasting
confidence: 99%
“…Sapuan and Roly found that economic growth is positively and significantly improved by fixed broadband subscriptions 9 . However, Yong Jing and Ab-Rahim found insignificant coefficients of this variable on GDP of ASEAN-5 countries, which can be explained by differences in analyzing methods and data collection 8 . In addition, it was found that different income groups have different effects of fixed broadband subscriptions.…”
Section: Fixed Broadband Subscriptionsmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, the positive impact of logistics was more pronounced in relatively underdeveloped provinces. Yong Jing and Ab-Rahim (2020) also found that telecommunications infrastructure positively impacted economic growth in both developed and developing countries. The above studies emphasize the necessity of green logistics and promote the operation of green logistics through continuous economic policies to obtain competitive returns, but fail to analyze the promotion of economic development in the process of green logistics operation.…”
Section: Literature Reviewmentioning
confidence: 91%